Everyday life in ancient Greece - Pearson, Anne. (New York : Franklin Watts, 1994)
Describes the everyday life of ancient Greeks--how they lived, played, worked, and fought.
Includes index.
Library Talk.
School Library Journal.
6.3
5-8
Keywords: Greece -- Civilization -- To 146 B.C. -- Juvenile literature; Greece -- Social life and customs -- Juvenile literature; Greece -- Civilization -- To 146 B.C.; Greece -- Social life and customs; Greece -- Civilization; Greece -- Social life and customs